MANAGEMENT OF MODERN HEALTHCARE - Ilyasova Munisa Mirvaliyevna; Razikova Aziza Abdumalikovna (Web of Journals Publishing, 2024)
For medical services the following is applied: monopoly prices (set by the manufacturer); nominal prices taking into account cost and minimum profitability; wholesale prices (large quantities of goods are sold to organizations at a significant discount); retail prices (in the store), taking into account acceptable markups and the benefits of the selling organization (seller); market prices (equal to retail prices) (determined by a group of selling entities, taking into account the overall benefit); sliding prices (set taking into account various conditions); fixed prices (determined by the state, consumer associations, contracts) [ 2 ].
Keywords: Marketing, public speaking, medicine employees